A systematic review of occupational radiation individual dose monitoring among healthcare workers exposed in Africa - Gbetchedji, A. Arnaud; Houndetoungan, Gilles David; AMOUSSOU-GUENOU, KUASSI MARCELLIN (My University, 2020)
Dosimetricmonitoringisusefultolimitexposurestoionisingradiationinmedical occupational settings, and reduce subsequent health risks. Scientific literatures, such as the UNSCEAR report 2017 and International Atomic Energy Agency Report 2014b, updated information on this subject; however, few African works have been found. This is the reason why we undertook this study, which summarises existing information on monitoring external radiation exposure doses for the whole body, using data from medical workers on this continent. Using standard terms and combining different keyword searches for radiation dose monitoring among radiology healthcare workers in Africa, from the titles, abstracts, and full texts, we found 3139 articles in the PubMed/MEDLINE, Google Scholar and INIS databases. Two reviewers screened the retrieved publications based on predefined eligibility criteria to identify relevant studies, extract key information from each, and summarise the data in table form. A total of 20 potentially relevant articles were identified. Among these 20 articles, 15 reported the overall average annual effectivedose. Studies included in this systematic review represent an inventory of the radiation protection of medical workers in various African countries, with a focus on the monitoring of occupational radiation exposure. The size of studied populations ranged between 81 and 5152 occupational exposed workers. The mean annual effective doses ranged from 0.44 to 8.20 mSv in all specialities of medical sectors, while diagnostic radiology ranged from 0.07 to 4.37mSv.Forthenuclearmedicineandradiotherapyfrommedicalgroups,the mean annual effective dose varied between 0.56 and 6.30 mSv. Industrial and research/teaching sectors data varied between 0.38 to 19.40 mSv. In conclusion,morestudiesimplementedondosimetricmonitoringinAfricaareneeded to get a real picture of occupational exposure in the continent.
Keywords: healthcare workers; dose monitoring; occupational radiation exposure; diagnostic radiology; diagnostic x-ray; medical imaging; Africa